بعض المتغيرات النفسية المسهمة في الالتزام المهني لدى معلمي المرحلة الابتدائية الأزهرية - زايد، هليل زايد هليل (جامعة طنطا - كلية التربية, 2023)
هدف البحث التعرف على إمكانية التنبؤ بالالتزام المهني من خلال المتغيرات النفسية (رأس المال النفسي، والتمكين النفسي، والرضا الوظيفي)، ومعرفة أي تلك المتغيرات أكثر إسهاما فيه، وكذلك الكشف عن الفروق في أبعاد الالتزام المهني في ضوء اختلاف (النوع، والخبرة، طبيعة التخصص)، وذلك على (٢٤٣) معلم ومعلمة من معلمي المعاهد الابتدائية بإدارة أبو حماد التعليمية الأزهرية بمحافظة الشرقية، واشتملت أدوات البحث على مقاييس الالتزام المهني (إعداد الباحث)، ورأس المال النفسي (إعداد الباحث)، والتمكين النفسي، والرضا الوظيفي، واستخدم الباحث تحليل الانحدار الخطي المتعدد، واختبار "ت" لمجموعتين مستقلتين، وتحليل التباين أحادي الاتجاه، واختبار شيفيه، وأشارت نتائج البحث إلى إمكانية التنبؤ بالالتزام المهني من خلال المتغيرات النفسية (رأس المال النفسي، والتمكين النفسي، والرضا الوظيفي)، وأن الرضا الوظيفي أكثر المتغيرات إسهاما في الالتزام المهني، وعدم جود فروق دالة إحصائيا في الالتزام المهني ترجع إلى اختلاف النوع، ووجود فروق دالة إحصائيا في الالتزام المهني ترجع إلى اختلاف سنوات الخبرة لصالح (الأكثر من 20 عام)، ووجود فروق دالة إحصائيا في الالتزام المهني ترجع إلى اختلاف طبيعة التخصص لصالح المؤهلين تربويا، كما أسفر البحث عن بعض التوصيات والمقترحات البحثية. The research aimed at verifing the possibility of predicting professional commitment through psychological variables (psychological capital, psychological empowerment, job satisfaction), and to know which of those variables contribute more to it, as well as to reveal the differences in the dimensions of professional commitment in the light of the difference (gender, experience, and nature of the specialization), on (243) teachers of primary institutes in the administration of Abu Hammad Educational Al-Azhar in Sharqiyah Governorate, and the research tools included measures of professional commitment (preparation of the researcher), psychological capital (preparation of the researcher), and empowerment Psychological, job satisfaction, the researcher used multiple linear regression analysis, the "T" test for two independent groups, the analysis of one-way variance, and the Schiffe test, and the results of the research indicated the predictability of professional commitment through psychological variables (psychological capital, psychological empowerment, job satisfaction), and that job satisfaction is the most contributing variable to professional commitment, and there were no differences in professional commitment due to gender, and there were statistically significant differences in professional commitment due to years of experience in favor of (more than 20 years), and there were statistically significant differences in professional commitment due to nature of the specialization in favor of educationally qualified people, and the research also resulted in some recommendations and research proposals.
Keywords: الالتزام المهني -- معلمو المرحلة الابتدائية -- رأس المال النفسي -- التمكين النفسي -- الرضا الوظيفي